Réponses

  • Utilisateur Brainly
2014-09-15T18:35:47+02:00
A= (3x - 1)² - 81
A= (3x - 1)² - 9²
A= (3x - 1 + 9)(3x - 1 - 9)
A= (3x + 8)(3x - 10)

B= (5x - 2)² - 16
B= (5x - 2) - 4²
B= (5x - 2 + 4)(5x - 2 - 4)
B= (5x + 2)(5x - 6)

C= 9 - (2x - 4)²
C= 3² - (2x - 4)²
C= (3 - 2x + 4)(3 + 2x - 4)
C= (- 2x + 7)(2x - 1)

D= (8x - 9)² - 1
D= (8x - 9)² - 1²
D= (8x - 9 + 1)(8x - 9 - 1)
D= (8x - 8)(8x - 10)

E= (3x - 4)² - (5x - 1)²
E= (3x - 4 - 5x + 1)(3x - 4 + 5x - 1)
E= (- 2x - 3)(8x - 5)

F= 3x² - 1
F= (√3x + 1)(√3x - 1)